How to Motivate Students to Submit the Homework Tasks on Time? - Dildora Gafurovna Ashurova (International Journal on Orange Technologies, 2022)
Completion of homework is a crucial learning process. Though it often takes place as an after-school activity, it presents multiple challenges for many students, especially for those who have got low level knowledge and lack of autonomous skills. In my exploratory action research I tried to explore the reasons of why do some of my teenage students at the academic lyceum come to the lessons without completing the homework. The data was collected from 24 students of both specialized and non-specialized groups in English, using quantitative and qualitative research. The findings show that, the reasons varied in those two groups. Accordingly, I implemented some changes in order to help my students to deal with those challenges and manage their homework more responsibly. My study offers new practical ways of motivating students in completion of their homework regularly.